SISTEM INFORMASI PELAYANAN ADMINISTRASI DESA KARANG DAPO BERBASIS WEB - Tandi Yunega; Marhalim Marhalim; Ujang Juhardi; Ar. Walad Mahfuzi; Andilala Andilala (Jurnal Media Infotama, 2023)
The rapid use of information technology today has made the government more aware of the benefits of using information technology, especially in the internet sector. The high use of the internet is inseparable from the emergence of various website applications developed by the community, entrepreneurs, including government agencies. The Central Government strongly supports the creation of various kinds of community service websites as an effort to keep the wheels of government running. The development of this community service website is an effort to prevent crowds at public service facilities which currently need to be avoided to prevent the transmission of the Covid-19 outbreak, which recently has not shown a significant decline. In terms of community services in rural areas, the central government also understands and encourages village governments to have village websites that can be used to empower villages and village communities, this is evidenced by the launch of the desa.id domain extension as an official domain extension and is devoted to websites. Village website development is also a government priority program contained in Permendesa Number 11 of 2019 concerning Priority for the Use of Village Funds in 2020 in Appendix I CHAPTER I Letter E concerning Priority List in the Village Development Sector, Point d concerning Procurement, Development, utilization and maintenance of facilities and infrastructure information and communication and item 2 mentions the creation of a village website. This shows that the central government is really serious so that villages can develop website-based services and information. Karang Dapo Village is one of the villages located in Sikap Dalamg District, Empat Lawang Regency, Sumatera Selatan Province. The constraints experienced by the Karang Dapo village government today are the limited access to information that can be seen and accessed by the village community in particular and the surrounding community in general, especially access to information on village activities, village administration, superior village products and village locations. Based on these problems, it encourages the author to create a website and administrative application for the Weskut village. With the existence of a village website and an online village administration application it is hoped that in providing services to the community it can be maximized, and access to information about the village of Karang Dapo can be accessed and seen by anyone and from anywhere while an internet network is still available.